Application of various processes to recycle lithium-ion batteries (LIBs): A brief review. (2021) - Mohanty, Archita; Sahu, Sibananda; Sukla, Lala Behari; Devi, Niharbala
Abstract: The growing concern for portable devices and electric vehicles has led to an enormous rise in the demand for lithium-ion batteries. After the end of life, these LIBs act both as a secondary source for the recovery of valuable metals and simultaneously possess a threat to the environment. So they need to be recycled properly to gain economic benefits. This article focuses on several methods used for the recycling of valuable metals. It describes the structures, components, and state-of-the-art on spent LIBs. This article has summarized different recycling methods, their physiochemistry, and their applications to regenerate valued metals like cobalt, nickel, lithium, etc. The advantages and the problems linked with these technologies have also been put forward.